Portraying those we condemn with care: extending the ethics of representation - Wright Monod, Sarah (Critical criminology, 2017)
The study of crime’s images is an increasingly important endeavour. In this paper I seek to understand the impact of an image of a criminal child (the outcomes and consequences that have stemmed from its display) by examining its affect (its capacity to engage its viewers). I demonstrate how the image’s meaning emerged from encounters with both the content and the format of the image, as well as from the context in which these encounters occurred. I will demonstrate that the impacts from this image went beyond what was necessary to punish, and propose that an ethics of representation is extended to include images of the condemned. For some population groups, this extension can mitigate the influence of fantasies about criminal ‘others’ that may come into play when pictures of them are viewed.